Studies on taxonomy and mutants identification by protein SDS-PAGE in Spirulina - WANG Zhi-ping (浙江大学学报. 农业与生命科学版)
The SDS-PAGE patterns of proteins, which extracted from Spirulina platensis by extractant containing SDS and purified by -20℃ actone, were clear and had many bands. The SDS-PAGE analysis of Sp-D, Sp-Y, Sp-F, Sp-J, Sp-B, Sp-S, Sp-K, Sp-Z and it's mutants: Sp-Z (S) and Sp-Z (L) showed that: (1) The protein bands of Spirulina mainly distributed from 31 kD to 188 kD, the patterns among strains were similar, but there were some remarkable differences, which could be valuable in the systematic taxonomic study of Spirulina: (2) The same protein patterns of Sp-J and Sp-K further indicated that they belonged to same strain; (3) Sp-Z (S) and Sp-Z (L) are the mutants from Sp-Z. A new 43 kD protein appeared on the pattern of Sp-Z (S) which could grow splendidly in sea-water media. And the 87 kD protein disappeared on the pattern of Sp-Z (L) with linear filaments; (4) The mechods of protein SDS-PAGE could be useful in the taxonomic study and mutant identification of Spirulina.